West-Life: A Virtual Research Environment for structural biology - Morris, Chris; Andreetto, Paolo; Banci, Lucia; Bonvin, Alexandre M J J; Chojnowski, Grzegorz; Cano, Laura Del; Carazo, José Marıa; Conesa, Pablo; Daenke, Susan; Damaskos, George; Giachetti, Andrea; Haley, Natalie E C; et al. (Journal of structural biology: X, 2019)
The West-Life project (https://about.west-life.eu/) is a Horizon 2020 project funded by the European Commission to provide data processing and data management services for the international community of structural biologists, and in particular to support integrative experimental approaches within the field of structural biology. It has developed enhancements to existing web services for structure solution and analysis, created new pipelines to link these services into more complex higher-level workflows, and added new data management facilities. Through this work it has striven to make the benefits of European e-Infrastructures more accessible to life-science researchers in general and structural biologists in particular.
Keywords: Structural biology; Cloud computing; Grid computing; Data management; Virtual Research Environment